Impact of tempering conditions on special spoilage, off-odor and the formation of volatile compounds in bulgur - Yilmaz, Betul Bay; Bayram, Mustafa; Turker, Nuzhet (ELSEVIER, 2025)
The spoilage of bulgur, characterized by a distinctive off-odor, poses a significant challenge to the bulgur industry, resulting in an annual production loss of 10 %. The tempering process plays a critical role to prevent this problem. This study investigated spoilage under high-moisture tempering conditions (15-27 % moisture, 25, 35 and 45 degrees C, 0-12 h), focusing on off-odor formation, volatile compounds and microbial activity. Extended tempering at elevated moisture contents and temperatures significantly (p <= 0.05) impacted product quality, causing off-odor, rancidity and microbial spoilage. Volatile compounds, including 2,3-butanediol, pentanal, hexanal, 4-vinyl-guaiacol, 2-methoxy-4-vinylphenol, were linked to off-odors. High moisture levels (25-27 %) accelerated microbial growth, with Aspergillus niger, Pseudomonas aeruginosa and Cronobacter sakazakii detected in deteriorated samples. Thiobarbituric-acid-reactive substances data indicated that lipid oxidation contributed to off-odor formation, highlighting the roles of lipid oxidation and microbial spoilage under these tempering conditions. These findings emphasize the importance of controlling tempering parameters to preserve bulgur quality.
Keywords: Bulgur; Tempering; Microbial deterioration; Off-odor formation; Volatile aromatic compounds; PSEUDOMONAS-FLUORESCENS; CANDIDA-SAKE; STORAGE; GROWTH; COLOR; CONTAMINATION; MYCOTOXINS; INDICATOR; RANCIDITY; COOKING; Food Science & Technology